137-OR: Trends in Lipid Levels Relative to Lipid-Lowering Drug Use among Danish Type 2 Diabetes Subjects - AMADID, HANAN; DUNBAR, MARIA BEKKER-NIELSEN; RØNN, PERNILLE F.; KNUDSEN, JAKOB S.; CARSTENSEN, BENDIX; PERSSON, FREDERIK; JØRGENSEN, MARIT E. (Diabetes (New York, N.Y.), 2020)
Background: Lipid-lowering treatment is crucial in preventing cardiovascular disease in type 2 diabetes subjects. It is unknown how well treatment guidelines translate into clinical practice. We examined measured lipid levels in relation to use of lipid-lowering drugs among type 2 diabetes subjects in Denmark from 2010 to 2017. Methods: The study population consisted of 404,389 subjects with type 2 diabetes living in Denmark between 1996 and 2017 identified using the Danish Diabetes Register. Redemptions of prescribed lipid-lowering drugs were ascertained from the nationwide Register of Medicinal Products Statistics. Data on lipid levels was sourced from the National Laboratory Database containing detailed information on laboratory measurements at major clinical laboratories since 2010. A drug-exposure function was developed and applied to examine follow-up of lipid-lowering drug coverage at any given time based on the redeemed amount and dose of lipid-lowering drugs. Annual mean lipid levels were obtained by calculating the mean lipid measurement value per subject, per calendar year, and per lipid type. Proportions of subjects within LDL thresholds were calculated according to thresholds defined by 2019 European Society of Cardiology dyslipidemia guidelines. Results: In total, 64% of subjects redeemed at least two prescriptions of lipid-lowering drugs during the study period. A decline in levels of total-cholesterol and LDL was observed in the years from 2010 to 2017 in users and non-users of lipid-lowering drugs. Annual mean LDL levels were lower among lipid-lowering drug users compared with non-users (in 2017: 1.84 and 2.57 mmol/L, respectively). A greater fraction of lipid-lowering drug users achieved the LDL goal of <1.8 mmol/L compared with non-lipid-lowering drug users (in 2017: 51.7% and 19%, respectively). Conclusions: Lipid-lowering drug use and LDL levels are far from optimal in the Danish type 2 diabetes population and constitute a large potential for improvement.